A General Method for the Specific Staining of Intracellular Antigens with Ferritin-Antibody Conjugates - McLean, J. D. (1970)
A general method is described whereby an intracellular macromolecule can be specifically stained with its antibody conjugated to ferritin. In this method cells or cell organelles are fixed, embedded in bovine serum albumin cross-linked with glutaraldehyde or formaldehyde, and then sectioned. This procedure preserves antigenic determinants as well as the cellular ultrastructure. The application of the ferritin-antibody conjugate to the section produces specific staining of the exposed antigen.